Transfer of orally administered ZnO:Eu nanoparticles through the blood–testis barrier: the effect on kinetic sperm parameters and apoptosis in mice testes. (21st August 2019) - Kielbik, Paula; Kaszewski, Jaroslaw; Dabrowski, Sebastian; Faundez, Ricardo; Witkowski, Barlomiej S; Wachnicki, Lukasz; Zhydachevskyy, Yaroslav; Sapierzynski, Rafal; Gajewski, Zdzislaw; Godlewski, Marek; Godlewski, Michal M
Abstract: Zinc-based nanoparticles are promising materials for various applications, including in biomedicine. The aim of our study was to determine the effect of fluorescent europium-doped zinc oxide nanoparticles (ZnO:Eu NPs) on sperm parameters, cell apoptosis and integrity of the blood–testis barrier (BTB) in mice. Nanostructures were orally administered to adult mice ( n  = 34). Animals were sacrificed after 3 h, 24 h, 7 d and 14 d following oral administration. Sperm was collected and analysed for viability and kinetic parameters. Collected testes were quantitatively analysed for accumulation of ZnO:Eu NPs. Microscopic evaluation based on immunofluorescence and histopathological studies were also conducted. Results showed that ZnO:Eu NPs were able to overcome the BTB with their subsequent accumulation in the testis. No toxic or pro-apoptotic effects of nanoparticles on the male reproductive system were observed. The results suggested that ZnO:Eu NPs were able to accumulate in the testis with no negative impact on sperm parameters, tissue architecture or the integrity of the BTB.